Does a single session of electroconvulsive therapy alter the neural response to emotional faces in depression? A randomised sham-controlled functional magnetic resonance imaging study - Miskowiak, K; Kessing, L; Ott, C; Macoveanu, J; Harmer, C; Jørgensen, A; Revsbech, R; Jensen, H; Paulson, O; Siebner, H; Jørgensen, M (SAGE Publications, 2017)
Negative neurocognitive bias is a core feature of major depressive disorder that is reversed by pharmacological and psychological treatments. This double-blind functional magnetic resonance imaging study investigated for the first time whether electroconvulsive therapy modulates negative neurocognitive bias in major depressive disorder. Patients with major depressive disorder were randomised to one active ( n=15) or sham electroconvulsive therapy ( n=12). The following day they underwent whole-brain functional magnetic resonance imaging at 3T while viewing emotional faces and performed facial expression recognition and dot-probe tasks. A single electroconvulsive therapy session had no effect on amygdala response to emotional faces. Whole-brain analysis revealed no effects of electroconvulsive therapy versus sham therapy after family-wise error correction at the cluster level, using a cluster-forming threshold of Z>3.1 ( p<0.001) to secure family-wise error <5%. Groups showed no differences in behavioural measures, mood and medication. Exploratory cluster-corrected whole-brain analysis ( Z>2.3; p<0.01) revealed electroconvulsive therapy-induced changes in parahippocampal and superior frontal responses to fearful versus happy faces as well as in fear-specific functional connectivity between amygdala and occipito-temporal regions. Across all patients, greater fear-specific amygdala - occipital coupling correlated with lower fear vigilance. Despite no statistically significant shift in neural response to faces after a single electroconvulsive therapy session, the observed trend changes after a single electroconvulsive therapy session point to an early shift in emotional processing that may contribute to antidepressant effects of electroconvulsive therapy.